The association between involuntary memory and emotional adjustment after childbirth. (27th July 2015) - Briddon, Emma; Isaac, Claire; Slade, Pauline
<x xml:space="preserve">Abstract</x> Objectives A woman's memory of her experience of giving birth can strongly influence her mental health, and the development of her relationship with her infant, in a positive or negative direction. Highly distressing, involuntary memories of the birth may indicate symptoms of post‐traumatic stress (PTS), which is increasingly recognized as a possible outcome of childbirth. Involuntary memories are not, however, exclusive to trauma and can also be experienced after positive events. This study sought to investigate involuntary memories for childbirth, as this is an event that is known to be potentially experienced both as highly positive and negative, and associated with a range of emotional outcomes, including greater well‐being and symptoms of PTS. Methods A total of 122 women completed a measure of their emotional experience of giving birth within 3 days of the event, and 65 of these women responded to a postal follow‐up at 6 weeks, with measures of involuntary memory experience, PTS symptoms and well‐being. Results Experiencing pleasant involuntary memories was more common than experiencing unpleasant involuntary memories of the birth. The frequency of these memories and how they were experienced as either distressing or enjoyable was associated with post‐partum emotional adjustment, demonstrated by the development of PTS symptoms or greater well‐being. Conclusions These results are important because to date, little research has examined the development of positive involuntary memories and their association with positive emotional adjustment. <boxed-text content-type="box" id="bjhp12151-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Positive and negative emotional experiences can coexist in childbirth. Involuntary memories after negative events can be associated with post‐traumatic stress. Involuntary memories can also occur after strongly positive events. What does this study add? Women can experience both positive and negative involuntary memories after childbirth. Involuntary negative memories mediate the link between birth experience and post‐traumatic stress. Positive involuntary memories are associated with greater well‐being in the post‐partum. Transformation of negatively experienced events into positively experienced involuntary memories may facilitate adjustment after childbirth. </boxed-text>